TRANSFORMATION OF LEARNING INTO ACTIVE PROCESS AND ITS OUTCOMES THROUGH THE USE OF ACTIVE METHODOLOGIES - Sousa, Rafael Lopes de; Carvalho Kiss, Daniella Vieira de; Dias, Luiz Antonio [UNESP] (Fundacao Univ Tocantins, 2022)
This article presents partial results of the project Transforming learning into an active process and its consequences through the use of active methodologies, organized by the Study Group: Experiences and dimensions of school knowledge. The group involves master's students from the Interdisciplinary Graduate Program in Human Sciences at Universidade Santo Amaro (PPGICH/UNISA) and aims to discuss the various aspects of literacy in an interdisciplinary approach, focused on the continuing education of teachers in the public network of the State from Sao Paulo. The text on screen presents results of the investigation of educational practices under an active dimension of learning, as well as the possibilities of using Active Methodologies in Professional and Technological Education. The analysis is supported by renowned authors in the area who show great interest in re-dimensioning educational praxis with a view to forming autonomous, creative students capable of learning how to learn. Considering the pandemic context and its deleterious effects on education, which made the interactions between the subjects involved in the teaching-learning process even more complex, the article presents some hypotheses and a new way of looking at educational practices with the use of active methodologies in Vocational and Technological Education.
Keywords: Transformation of Learning; Active Methodologies; Professional Education